Impactos da política fiscal e tributária no crescimento econômico - Louro, Antonio Carlos Castro (2015)
Using an adaptation of Telles and Mussolini model (2014), this paper aims to discuss the characterizations of the tax code, discussing how the changes in the tax code could impact fiscal policy. Is discussed on the basis of tax differentiation into five groups, namely: payroll taxes, investment taxes, consumption taxes, income and wealth taxes, and taxes on international trade, from which it is argued that their impacts fiscal policy, for the interaction of economic variables and the evolution of these variables, as well as the relationship between preference for a particular tax structure and the debt of a country. After the theoretical discussion, it is a descriptive analysis of the evolution of these variables for each tax tax category, relating to its evolution in time for a group of 64 countries, taken from the work of Telles and Mussolini (2014) and linking their intertemporal evolution. Finally, it is an analysis of the tax structure of these countries, arguing, in the analysis of panel data, the results for the estimates of fixed effects models and random effects, the estimation results for the Arellano-Bond model, and utilizando- the instrumental approach the Generalized Method of Moments, which concludes that the tax on wealth and taxes on international trade for purposes of financing the excess government spending impacts negatively on the growth path, among other results.